DETERMINAN KEBIJAKAN DIVIDEN PADA PERUSAHAAN SUBINDUSTRI MAKANAN OLAHAN DI INDONESIA - Delvia Okvi Alfionita; Kertati Sumekar; Rozaq Muhammad Yasin (Jurnal Riset Ilmu Ekonomi, 2023)
This study aims to analyze the impact of the company’s internal factors on dividend policy in processed food sub-industry companies in Indonesia. The internal factors that determine the dividend policy tested in this research are Collateralizable Assets, Investment Opportunity Sets, Lagged Dividend, and Debt Policy. This research uses a quantitative approach, using secondary data derived from the financial reports of processed food sub-industry companies listed on the IDX for the 2016-2021 periods. Purposive sampling method was used to obtain a sample of 13 companies from a population of 24 companies. The data analysis technique used is panel data regression. The results showed that partially Investment opportunity set, lagged dividend, and debt policy had a positive and significant effect on dividend policy. Meanwhile Collateralizable Assets have no significant effect on dividend policy.